Irrigation strategies for optimal use of saline water in Mediterranean agriculture - Crescimanno G.; Garofalo P. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
In this paper management strategies optimizing irrigation and also reducing the risk of secondary salinization were explored for seven Sicilian soil profiles by using the SWAP model. Two viable options addressing constraints of limited water availability were simulated for the seven soil profiles. These options were (i) different irrigation scheduling, i.e. irrigation with a fixed amount of water but different number of irrigations and (ii) cyclic strategies, i.e. alternating two irrigation waters having different salinity. Analysis of three different irrigation scheduling evidenced that making a limited number of irrigations (two in our case), using larger application volumes, determined a lower risk of salinization. With reference to the role of cracks in the process of salt-leaching, the simulations performed indicated that water stored in cracks promoted leaching of the accumulated solutes and that neglecting the presence of cracks led to overestimating salinization. Cyclic proved to be the best management option to be suggested to reduce the risk of salinization. Findings concerning the role of cracks in the process of salt-leaching suggested that, under field conditions, application of a leaching solution was more efficient if the soil presented a considerable degree of cracking.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)